Have There Been any Changes in the Epidemiology and Etiology of Maxillofacial Trauma During the COVID-19 Pandemic? An Italian Multicenter Study. Issue 4 (19th June 2021) - Salzano, Giovanni; Dell'Aversana Orabona, Giovanni; Audino, Giovanni; Vaira, Luigi Angelo; Trevisiol, Lorenzo; D'Agostino, Antonio; Pucci, Resi; Battisti, Andrea; Cucurullo, Marco; Ciardiello, Cristina; Barca, Ida; Cristofaro, Maria Giulia; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a significant impact on people's behavior. The aim of this study has been to evaluate how the SARS-CoV-2 pandemic has impacted the incidence and the features of maxillofacial fractures presented at 6 Italian tertiary centers. Clinical records of all the patients diagnosed for facial fractures between February 23 and May 23, 2019 and 2020 were retrospectively reviewed. Any differences in patient number and characteristics and fracture etiology and site between the 2 groups were then statistically analyzed. There has been a 69.1% decrease in the number of incoming patients during the pandemic. The number of foreign patients has decreased significantly (23.3% versus 9.6%, P  = 0.011) while the average age has increased (38.6 versus 45.6 years old, P  = 0.01). Specific statistical significant differences for accidental falls (31.8% versus 50.1%, P  = 0.005) and sports injuries (16.9% versus 1.4%, P  < 0.001) were found. Concerning fracture sites, significant differences have been found in relation to nasal (22.5% versus 11.4%, P  = 0.009) and frontal sinus (0.9% versus 4.4%, P  = 0.037) fractures. In conclusion, SARS-CoV-2 pandemic has significantly changed the epidemiology and the etiology of facial traumas.